New Open Economy Macroeconomics: Evidence from an Empirical Test on South Asian Economic Data - Paudel, Bamadev (NRB Economic Review, 2011)
This study first conducts a detailed survey on recently emerged new field in economics called new open economy macroeconomics and then carries out an empirical test of theoretical predictions of these models to observe transmission effects of Indian economic shocks in South Asia region. In the survey, the study starts with the seminal work of Obstfeld and Rogoff (1995) and then evaluates the subsequent evolution of this field. The survey reveals that the field is rapidly evolving with many dimensions added on it within a short period of time, making this field richer and betterable to perform better predictions. The estimation of Vector Autoregression model for South Asia region, on the other hand, uncovers that the effects of Indian shocks in South Asia region, have mixed results. Since the real, nominal, and financial shocks generated in India affect the economies of neighboring countries with varied extent.